CONCEPTUALIZATION OF THE QALB AS AN EFFORT TO FORM A SCALE OF MEASUREMENT IN ISLAMIC PSYCHOLOGY - Nugraha, M. Fadli (Psikis : Jurnal Psikologi Islami, 2022)
The purpose of this research was to explore the concept of qalb which is explained in the Al-Quran in order to describe qalb according to the wishes that explain qalb, in this case is the Al-Quran. The research question was whether qalb in the Qur’an can be conceptualized based on the Qur’an and sunnah (hadith that explain the Qur’an). This study used a qualitative method with a descriptive approach to the Qur’an with the Qur’an. The primary data in this study were the Al-Quran and sunnah (hadith that explain the Qur’an) while the secondary data in this study were from books and journals whose explanations are related to qalb. The results of this study have theoretically proven that qalb can be conceptualized based on the Al-Quran and sunnah (hadith which explain the Al-Quran). It is hoped that the results of this research can be followed up by operationalizing based on the findings in this study to build a qalb measurement tool that have not been found around the world. Across-sector collaboration is also needed to continue this research which must also prioritize the Qur’an rather than human opinion so that it is clear to distinguish psychology in general from Islamic psychology.